2012
DOI: 10.2139/ssrn.2334224
|View full text |Cite
|
Sign up to set email alerts
|

Financial Stability and Central Bank Governance

Abstract: The financial crisis has ignited a debate about the appropriate objectives and the governance structure of central banks. We use novel survey data to investigate the relation between these traits and banking system stability, focusing in particular on their role in micro-prudential supervision. We find that the separation of powers between single and multiple bank * We are grateful to Franklin Allen, Mats Bergman, Mathias Dewatripont, Francesco Giavazzi, Iman van Lelyveld, Enrico Perotti, Marco Pagano, Roberto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 31 publications
0
13
1
1
Order By: Relevance
“…In contrast with both studies, Koetter et al (2014) find no effect of a number of central bank supervision (as well as of a number of other central bank's institutional traits) on NPLs, suggesting that the policy discussion on the allocation of supervision might be misguided.…”
Section: Related Literaturecontrasting
confidence: 92%
See 2 more Smart Citations
“…In contrast with both studies, Koetter et al (2014) find no effect of a number of central bank supervision (as well as of a number of other central bank's institutional traits) on NPLs, suggesting that the policy discussion on the allocation of supervision might be misguided.…”
Section: Related Literaturecontrasting
confidence: 92%
“…Existing evidence, however, is mixed and provides no clear-cut answer on this relationship. This led some researchers to cast doubt on the presence of a link between supervisory governance and financial stability (Goodhart and Schoenmaker, 1995;Koetter et al, 2014). Nevertheless, most empirical works focused on the binary choice between a central bank or a separate agency as supervisor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Merrouche and Nier (2010) found that the buildup of banking imbalances (measured by the ratio of loans to deposits) was less severe where the CB had full control of supervision and regulation. However, Koetter, at al. (2014) finds no improvement in the credit risk or non-performing loan ratio at banks when the CB is also the PR in 44 countries.…”
Section: Ability To Implement Macroprudential Policiesmentioning
confidence: 99%
“…For example, the CBs in Iceland, Luxembourg, Sweden, and the U.K. provide analysis or consult with the authority for setting the CCyB and thus can have an influence even if it does not have the authority itself to set the CCyB. 7 See Nier, Osinski, Jacome, and Madrid (2011),Goodhart and Schoenmaker (1995), andMerrouche and Nier (2010) as examples of papers that find that the CB being the PR leads to better banking-sector outcomes andKoetter, Roszbach, and Spagnolo (2014) as an example of a paper that does not find this result.…”
mentioning
confidence: 99%